Ecology and economy in the Arctic. Uncertainty, knowledge and precaution - Iulie Aslaksen; Solveig Glomsrød; Anne Ingeborg Myhr (Statistics Norway, Research Department, 2007)
Climate change impacts in the Arctic require that complex relationships between the economy, the environment, and the living conditions of indigenous and local people be taken into account. While traditional approaches to economic valuation may not be sufficient to capture these relationships, the research area of ecological economics suggests broader approaches to environmental uncertainties, taking into account ethical values and conflicts of interest. Increased activity in petroleum exploration, manufacturing, transportation, tourism and other services have the potential to alter the Arctic environment and societies considerably. Application of the precautionary principle is suggested as a way to manage situations with large degrees of environmental uncertainty and potentially irreversible consequences. Precautionary approaches require the development of processes for acknowledgement of uncertainties, facilitation of stakeholder participation, recognition of ethical values, and taking into account the traditional ecological knowledge of indigenous people of the Arctic. Combining traditional and scientific knowledge about nature is an important part of understanding the resilience capacity of ecological and social systems, and of enhancing the potential for sustainable development.
Keywords: Q54; Q57; 330; Arctic; Environmental uncertainty; Ecological Economics; Precaution